NATION BRANDING KOPI ARABIKA KINTAMANI (Studi Kasus: Kopi Gunung Catur, Desa Catur, Kintamani, Bangli) - Sukiada, Ni Wayan Rainy Priadarsini; Parameswari, Anak Agung Ayu Intan (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 14 No 1 (2020): Vol. 14 No. 1, 2020, 2020)
Kopi Gunung Catur is a brand of specialty Arabica coffee that from Kintamani. This coffee brand has the export quality. This brand is cultivated by the farmer group named Subak Abian Tri Guna Karya. Today, branding has a significant role on the promotion in the international market. The Indonesian government began to build a nation brand for Indonesia Arabica coffee to avoid the claims from other countries and to expand market access. Likewise for Kopi Gunung Catur, there should be a proper strategy to improve the image of this coffee so its market access is increasingly wide open. Anholt said there are three strategies that can improve a country's product image, namely competence, contribution and communication. Kopi Gunung Catur that has been certified by Geographical Indications (IG) shows the ability of the farmers in Catur Village to cultivate coffee with good quality. Because it is cultivated organically, it enhances Indonesia's image worldwide about environmental protection. The philosophy Tri Hita Karana which is used as a cornerstone of its cultivation which synergizes human behavior and maintains the balance of nature strengthens the image of this coffee to the preservation of the nature. Kopi Gunung Catur has fulfilled the competency and contribution strategy. However, market access is still complained by Kopi Gunung Catur’s farmers and coffee makers. Through the qualitative descriptive method, it is found that there is still only small effort to develop a third nation branding strategy, namely communication. The communication strategy contributes greatly in supporting the market access, especially for export activities. Entering the industrialization era 4.0, mastering Information Technology (IT) and having the spirit of modern entrepreneurship is the main strategy to develop export activities. This is not optimally boosted by farmers and entrepreneurs of kopi Gunung Catur. So through this research it was found that the use of technology and modern entrepreneurial spirit (technopreneurship) as the communication based strategy became a right step in increasing export opportunities for Kopi Gunung Catur producers.